A new carbon-black/cellulose-sponge system with water supplied by injection for enhancing solar vapor generation. Issue 30 (15th July 2019) - Liu, Shang; Huang, Congliang; Huang, Qiangqiang; Wang, Fengchao; Guo, Chuwen
Abstract : The emerging solar vapor generation technology is becoming one of the most promising solar photothermal conversion technologies, which could relieve fresh water shortage. Abstract : The emerging solar vapor generation technology is becoming one of the most promising solar photothermal conversion technologies, which could relieve fresh water shortage. The traditional way of water supply in solar vapor generation systems is through sucking water directly from bulk water by capillary force, which cannot regulate the water injection rate to accommodate the changing outdoor irradiation density for a high evaporation efficiency. In this work, we investigated a unique carbon black-cellulose sponge system with water injected rather than absorbed from bulk water. The evaporation efficiency of this system (about 91.5%) was about 10% higher than that of a traditional one under 1 kW m −2, resulting from the reduced energy losses by matching the mass of injected water with the incident energy reasonably. The average evaporation efficiency of our system working outdoors was as high as 89.1%, when the solar irradiation density was varied between about 0 and 1350 W m −2 . We also find that the evaporation efficiency under an irradiation density of 200 W m −2 could reach about 112%, due to the lower surface temperature than the ambient one. Besides the common strategy of enhancing solar irradiation densities to improve evaporation efficiency, lowering solar irradiation densities may also be a good choice for enhancing the evaporation efficiency. Considering the low cost, simple preparation, excellent thermal management and high evaporation efficiency, we conclude that the black-cellulose sponge system with water injection could provide an effective way for vapor generation.